Gulong ng Buhay: A Correlation of Female Gender Preference in Driving Tricycle - Sierto, Maricel E.; Navarro, Ricky J. (Future Science / FSH-PH Publications, 2024)
The study’s primary goal was to identify the challenges and difficulties faced by female tricycle drivers in earning a living and the acceptance of the community for female tricycle drivers. In particular, this study sought answers to the following questions: (1) How long do female drivers ride tricycle as their means of earnings? (2) What are the reasons of female gender in driving tricycle as means of earning a living? (3) What are the advantages of female gender as tricycle driver? and (4) What are the disadvantages of female gender as tricycle driver? The study will use qualitative research design in which researchers will gather data through interviews. The results show that (1) Most drivers drive tricycles to earn a living; (2) In order to provide for their families, female tricycle drivers strive to assist their husbands. It's mainly family motivation that drives them. Every effort has been made to ensure that their children have a good life. In addition, they are able to provide for their families' financial needs and the care of their children; (3) In spite of the difficulties and obstacles encountered on the road, female tricycle drivers can improve safety for passengers by proving that they are able to drive as well as their male counterparts while remaining brave enough to continue driving; and (4) The challenges faced by female tricycle drivers included being able to make ends meet, balancing work and family obligations, encountering discrimination and stereotypes in other people as well as today's lifestyle.